AREAL AND ETHNOLINGUISTIC STUDY OF THE FOOD LEXICAN OF KUMKURGON DISTRICT - Davronova, Mukhlisa (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the role of the ethnic factor and phonetic patterns in the formation of food vocabulary in the Kumkurgan district of the Surkhandarya region. The object of the study is the names of food in the dialects of the main ethnic groups of the region — the Kungrat and Yuz tribes. The article highlights the areal-linguistic boundaries of local lexemes, as well as phonetic phenomena such as synharmonism, labialization, and vowel reduction.